Resveratrol atenua o estresse oxidativo e a lesão muscular de ratos sedentários submetidos à exercício físico - Narciso, Luis Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Physical inactivity is a public health problem and one of the greatest evils of modern society. Biggest part of the sedentary population practice physical activity sporadically. It is well established that the excess of physical exercise in or non-conditioned people causes oxidative stress and muscle damage. The present study tested the hypothesis that a single session of physical exercise can cause oxidative stress and muscle damage in sedentary rats. Additively, the antioxidant effect of the polyphenol resveratrol (RV) was evaluated, and its ability to attenuate oxidative stress and muscle damage caused by physical activity. For this, 40 sedentary adults rats (Rattus norvegicus Albinus, Wistar) were randomly subjected or not to 90 minutes of swimming, with and without treatment with RV (100mg/kg/14days): N-RV- (n=10) group maintained at rest and not treated with RV, N-RV+ (n=10) group maintained at rest and treated with RV, N+RV- (n=10) group subjected to physical exercise of swimming not treated with RV and N+RV+ (n=10) group submitted to physical exercise of swimming and treated with RV. In sedentary rats, physical activity of swimming promoted oxidative stress (observed by increased lipid peroxidation and decreased total antioxidant capacity of plasma) and significant increase in plasma activity of creatine kinase (CK) and lactate dehydrogenase (LDH). The RV treatment decreased lipid peroxidation and activity of the markers of muscle injury (CK and LDH) in sedentary rats submitted to swimming. This is one of the first evidence that a single session of physical exercise can cause oxidative stress in sedentary individuals and that the RV can be an alternative to alleviate muscle injury caused by this stress
Keywords: Antioxidantes; Natação; Stress oxidativo; Rato; Exercícios físicos aquáticos; Resveratrol